1994
DOI: 10.1021/jo00084a022
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Substitution of Dinitroolefins with 1,2-Difunctional Ethanes

Abstract: Reactions of ajS-dinitroolefins with 1,2-ethanedithiol form five-membered ring products. Similarly, reactions of ,/8-dinitroolefins with 2-mercaptoethanol give five-membered ring products along with monosubstituted olefins and products disubstituted on one carbon. The formation of cyclic products from a,d-dinitroolefins and 1,2-difunctional nucleophiles is explained in terms of a stepwise additionsubstitution mechanism in which a carbanion intermediate must be assumed. A Michael-type reaction seems to occur, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Verbindungen des Typs 8, die daher u.a. als 1,3-Ketoaldehyd-Synthons aufge-fal3t werden konnen, sind bislang kaum dargestellt worden [38].…”
Section: Thf -7andcunclassified
“…Verbindungen des Typs 8, die daher u.a. als 1,3-Ketoaldehyd-Synthons aufge-fal3t werden konnen, sind bislang kaum dargestellt worden [38].…”
Section: Thf -7andcunclassified
“…However, the regioselectivity of this transformation might be difficult to control, as the reactivity at the α - and β -positions of electrophile 1 is the balance of electron property and steric hindrance . Previous studies have demonstrated that both of these positions are reactive toward nucleophilic partners . In addition, even if the stereocontrol of the double bond geometry has been generally well-mastered in previous studies, the control of the enantioselectivity of this S N V reaction is much more challenging…”
mentioning
confidence: 99%